Examples of Constructions with the Simple Topological English Prepositions in and at Expressed in Selected Slavic Languages - Chłopek, Dorota (Slavia Centralis, 2020)
The objects of study in this paper are selected English expressions with the simple topological prepositions in and at expressed in the following Slavic languages: Polish, Czech, Slovene, Serbian and Croatian. Simple locational, topological relations which the English language encodes through two separate prepositions in and at tend to be constructed by a single form in many Slavic languages. The concerns of the paper are selected English constructions expressing physical coincidence through in and functional coincidence through at, rendered into the five Slavic languages, where the scenes may not include the difference in dimensionality existing in the source expressions, which causes many translational problems.